KEBIJAKAN RETROAKTIF DALAM PENEGAKAN HUKUM TERHADAP PELANGGARAN HAK ASASI MANUSIA YANG BERAT - Ahmad Basuki (Perspektif, 2007)
The article entitling “The Retroactive Policy in the straightening of law to the gross violation of Human Right in Indonesia" at to know according between retroactive Policy in the straightening of law to the gross violation of human right with The Indonesia rule of law character. According to the result of referential, we can make solution, first, that legality principle have to domicile very sturdy in regulation of Indonesia laws, event in the constitution and also law story level. Second, that retroactive policy in the Undang-undang No. 28 Tahun 2000 if it is observed in rechmatigheid aspect, it don’t reflected mirroring of execution of the rule of law. But if we observe it in the doelmatigheid aspect, we will find out similar with justice which is dominated by human principles in justice and civilized of Pancasila.